Efeitos da formulação mucoadesiva com extrato de Curcuma longa L. em animais portadores de mucosite intestinal induzida por 5-fluorouracil - Santos Filho, Edvande Xavier dos (2014)
Introduction: Intestinal mucositis is a frequent limiting factor in antineoplastic therapy. There is no truly effective treatment targeted to cure this side effect. Curcuma longa L. has been reported to have antioxidant, antitumor and anti-inflammatory properties. Objective: This study aimed to evaluate the effects of a mucoadhesive formulation with Curcuma longa L. extract (MCL) in mice bearing intestinal mucositis induced by 5-FU. Methods: Swiss male adult mice (35-40g) were randomly allocated into three experimental groups of 5 animals each: control (mucoadhesive formulation 0.6mL/animal, via gavage, from day 1-6); exposed to 5-fluorouracil (5-FU 200mg/kg, i.p., in days 4-6); treated prophylactically and throughout mucositis with FMCL and exposed to 5-FU (MCL 15mg/kg, via gavage, from day 1-6, plus 5-FU 200mg/kg, i.p., in days 4-6). In the 7th day, animals were anesthetized by xylazine-ketamine followed by cervical dislocation. Duodenal samples, 10 cm after pyloric sphincter were removed to perform the essays. The parameters evaluated were: body weight assessment, morphometrics and histo-pathological analysis, apoptosis (p53/Bax, Bcl-2), cell proliferation (Ki-67), myelo-peroxidase (MPO) and malondialdehyde (MDA). Results: 5-FU induced intestinal mucositis characterized by villus shortening, crypt deepening, intense inflammatory infiltration, vacuolization and mucosal edema. Besides, 5-FU induced severe mice body mass reduction, apoptosis in cells of villus and crypts (p<0.001), increase in MPO activity and MDA formation (p<0.05), when compared to the control group. Treatment with MCL attenuated body mass loss, protected intestinal mucosa from villus shortening and crypt deepening, decrease MPO activity and MDA formation (p<0.05). In this group of animals was also observed high expression of the cell proliferation marker Ki-67 in epithelial cells lining of villus and crypts. Conclusion: Our data confirm the therapeutic potential of MCL for the treatment of intestinal mucositis in mice. Further studies are needed to assess this formulation potential for human use.